A Partnered Approach to Opioid Management, Guideline Concordant Care and the Stepped Care Model of Pain Management - Dorflinger, Lindsey (J Gen Intern Med, 2014)
BACKGROUND: Pain is the most common presenting problem in primary care. Opioid therapy (OT) for chronic pain has increased dramatically over the past decade, as have related negative outcomes. Despite the development and dissemination of policy and clinical practice guidelines for pain management and OT, adoption has been variable. The Veterans Health Administration (VHA) has established a Stepped Care Model of Pain Management (SCM-PM) as an evidence-based framework and single standard of pain care to promote guideline-concordant care, but to date its adoption and related outcomes have not been systematically examined. OBJECTIVE: Our aim was to examine changes in care for Veterans receiving long-term OT for management of chronic pain over a four-year study period. DESIGN: As part of a comprehensive implementation evaluation of performance improvements, the current evaluation reports performance improvement outcomes related to pain management and OT over a four-year period. SUBJECTS: We studied Veterans receiving long-term (90+ consecutive days) OT through primary care. INTERVENTIONS: We engaged an interdisciplinary clinical-research team to develop and implement a multifaceted performance improvement approach that included interactive educational strategies and other organizational initiatives. MAIN MEASURES: We measured the proportion of patients receiving long-term OT; use of opioid risk mitigation strategies; referrals to pain-related specialty services; and use of non-opioid analgesics. KEY RESULTS: The proportion of patients receiving high-dose opioids decreased over four years (27.7 % to 24.7 %). The use of opioid risk mitigation strategies increased significantly. Referrals to physical therapy and chiropractic care and prescriptions for topical analgesics increased significantly, while referrals to the pain medicine specialty clinic decreased. CONCLUSIONS: We demonstrate improvements in the management of veterans receiving OT that are consistent with the SCM-PM and published practice guidelines. We highlight how partnerships among funders, researchers, clinicians, and administrators contributed to the project’s design and implementation, and to the dissemination strategy and future directions for improving opioid management and pain care.